218. Jarvik2000 and radiotherapy. Irradiation with high-energy photon beams and first results. (December 2018) - De Lorenzo, R. Giménez; Navarra, R.; Marinelli, D.; Adorante, N.; Giancaterino, S.; Genovesi, D.; Giammarco, G. Di; Falco, M.D.
Abstract : Purpose: Ventricular Assist Device (VAD) improves quality of life, but in patients requiring also radiotherapy its performance might be conditioned. We attempted measurements of basic operating parameters in vitro setting under high-energy photon beams with Jarvik2000 VAD. Methods: Jarvik2000 was a turbine pump (diameter = 2.5 cm, length = 5.5 cm, weight = 85 g) with neodymium-iron-boron magnet impeller supported by ceramic bearings and housed inside a titanium-welded shell. Implanted in left ventricle, the VAD made blood flow into the descending thoracic aorta and ensured perfusion of the organs by alternating two operating states: S1 (high-speed in 64 sec.) and S2 (low-speed in 8 sec). The device was connected to an external FlowMaker controller delivering power via a tunnelled driveline from a lithium ion battery. The in vitro setting consisted of a RW3 phantom with Plexiglas siliconized box filled with deionized water containing the pump. This was located and irradiated at the isocenter of a Synergy Agility (Elekta, Crawley) using 10MV photon beam, 1000 M.U. and a 20 × 20 cm 2 field. Voltage, current and frequency parameters of VAD alternating power supply were first measured to establish reference values in the BaseLine session. Then they were compared to those obtained immediately before, during and after irradiation ("PreRad", "Irradiation" and "PostRad" sessions respectively) and finally two months later ("Final Verification" session). Results: No changes were recorded in the registered parameters after each session. The VAD system worked stably. Figure shows both behaviour of voltage(mV), current(mA) and frequency(Hz) in S1 and S2 operating states during BaseLine session(a) and voltage(b), current(c) and frequency(d) of the five sessions during S1 state. Conclusions: VAD system continued its proper work after irradiation. To guarantee VAD functionality for any type of dose, future measurements will be carried out by simulating some typical radiotherapy treatments using 18MV photon beams to see whether neutron activation affects the components of the system.